The structure dependence of grain boundary passivation of Alloy 690 in high temperature water - Feng, Xingyu; Zhang, Shihao; Liu, Pengshuai; Kuang, Wenjun (Acta materialia, 2023)
The oxidation behavior of grain boundaries (GBs) was investigated on Alloy 690 after exposure to simulated pressurized water reactor primary water. The tendency to form passive film above GB is positively related to Cr diffusivity along GB which is determined by GB structure. Highly-ordered GB like twin boundary is subject to penetrative oxidation as Cr diffusivity is very low. GBs with misorientation angle θ ≤17.4° can't support fast diffusion of Cr either and also show penetrative oxidation. When θ ranges between 17.4° and 28.7°, Cr diffusivity is enhanced a little and GB shows unstable passivation. Meanwhile, the Cr diffusivity along GB is also related to the atomic packing density of GB planes. GB with higher atom packing density exhibits lower Cr diffusivity and deeper intergranular oxide depth. As θ increases above 28.7°, Cr diffusion is fast enough to support the formation of protective film above GB. [Display omitted]